Development of student worksheet for blended learning based guide inquiry and science process skill in reduction and oxidation reaction - Sinda Febrilia Miharti; Harizon Harizon; Zurweni Zurweni (Pascasarjana Universitas Negeri Medan, 2021)
This study aims to determine how the procedure for developing blended learning worksheets based on guided inquiry models and science process skills on the material of reduction and oxidation reactions in SMK. The method used in this research is to follow the Lee and Owens development model consisting of 5 stages of development, namely Analysis, Design, Development, Implementation and Evaluation. Analysis includes analysis of needs, characteristics of students, objectives, materials and technology. Design, researchers determine the schedule and development team, median specifications, prepare materials and make Flowcharts and storyboards. Development, develop LKPD according to storyboards, validated by material and media experts, and assessed by the teacher. Implementation includes group trials and effectiveness tests. Evaluation of LKPD in accordance with test results. Keywords: Blended learning, Guide inquiry, Reaction of reduction and oxidation, Science process skill, Student worksheet